Learning Design of Set Material in 7th Grade using Demak Bintoro Traditional Market Context - Cholidah Hanum; Farida Nursyahidah; Aurora Nur Aini (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
The set is one of the important materials for students. However, in reality, many students still experience some difficulties in learning the set material, especially on the concept of set operations. So we need the right media and context in learning mathematics on set material. Therefore, this study aims to develop a learning trajectory using the traditional market of Demak Bintoro as a context in the learning process using the Indonesian Realistic Mathematics Education (IRME) approach. The research method used is design research, which consists of three stages: preliminary design, experimental design, and retrospective analysis. The result of this research is the design of the learning trajectory of the set material using the traditional market of Demak Bintoro. This learning path consists of 4 activities, namely observing the interactive video of the Demak Bintoro traditional market to explain the meaning of sets, explaining subset universes and describing Venn diagrams, explaining set operations on (slice and union), and solving contextual problems related to set operations. The results of this study indicate that the use of the context of the Demak Bintoro traditional market can stimulate students' conceptual understanding of the set material. Furthermore, the results of this study are expected to be used as inspiration for exploring other local wisdom that can be used as a context in learning mathematics. Keywords: design research, set operation, learning trajectory, Demak Bintoro traditional market, IRME.